N, O site functionalized COFs adsorption material as well as preparation method and application thereof
Through the preparation of N,O site functionalized COFs materials, and using their chelation coordination interaction with thorium ions, the problems of poor stability and low selectivity of thorium ion adsorption in the prior art are solved, and efficient and fast Thorium ion removal and highly selective adsorption are suitable for complex wastewater treatment and show good recycling performance.
Patent Information
- Application Number
- CN202411036788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-07-31
AI Technical Summary
In the adsorption of existing solid adsorbents, there are problems of poor stability, low selectivity and low adsorption capacity, and it is difficult to efficiently remove thorium ions.
Using N,O site functionalized covalent organic framework (COFs) materials, the covalent bonding of aldehyde-based monomer and amino monomer is prepared to produce thorium adsorption materials with excellent adsorption properties, using their N,O double teeth The site interacts with the thorium ions in chelation coordination to achieve rapid adsorption and high selectivity.
It realizes rapid removal and efficient adsorption of thorium ions, has high metal ion selectivity and adsorption capacity, is suitable for thorium-containing wastewater with complex components, and maintains strong adsorption performance after multiple cycles of regeneration.
Smart Images

Figure CN119143955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemistry and environmental technology, and in particular to an N, O site functionalized COFs adsorption material and a preparation method and application thereof. Background Art
[0002] As an efficient and sustainable energy source, nuclear energy plays a huge role in the world's energy structure. How to actively promote the recycling of spent fuel is the key to ensuring the sustainable development of nuclear energy. Thorium is recognized as a very promising nuclear fuel. Therefore, in the process of spent fuel reprocessing, efficient and highly selective recovery and separation of thorium is an effective way to achieve full utilization of nuclear fuel.
[0003] In recent years, various techniques such as precipitation, ion exchange, adsorption, membrane filtration and electrochemical methods have been used to separate and enrich radionuclides. Among them, the solid adsorption method has been widely concerned due to its advantages such as simple operation and high cost-effectiveness. So far, several solid adsorbents have been reported for the adsorption and separation of Th (IV) ions, such as porous carbon, zeolite, metal organic framework materials (MOFs), etc. The literature Journal of Radioanalytical and Nuclear Chemistry, 2016, 310: 597-609 reported a high-silicon zeolite NKF-6 as a thorium adsorbent, and when the initial concentration was 33ppm, its saturated adsorption capacity was only 39mg / g. And because the zeolite material is mainly based on ion exchange, its adsorption selectivity is low, and a large amount of waste solids will also be generated. The literature ACS Applied Materials & Interfaces, 2017, 9(41): 36026-37 reported a magnetite-based metal-organic framework material (Fe3O4@AMCA-MIL53(Al)) for removing U(VI) and Th(IV) ions from water environments. Due to the poor stability of MOFs materials, the structure easily collapses under acidic conditions, making Fe3O4@AMCA-MIL53(Al) almost non-adsorbed at pH = 1.0 to 5.0. At pH = 6.0, the adsorption capacity for Th(IV) and U(VI) is only 25 and 23 mg / g, respectively.
[0004] Covalent Organic Frameworks (COFs) are an emerging class of porous crystalline polymers connected by covalent bonds. The building blocks of COFs can be designed and adjusted at the molecular level to optimize the framework structure and surface properties, giving them excellent adsorption capacity. However, although some pioneering results of COFs for radionuclide adsorption have been reported, porous materials that show efficient adsorption of Th(IV) in practical applications are still very rare. This is mainly because strong competitive adsorption requires that the porous material must have a unique affinity for thorium ions and needs to overcome the serious interference of other metal ions. Summary of the invention
[0005] In view of this, the present invention proposes an N, O site functionalized COFs adsorption material and a preparation method and application thereof to solve the problems of poor stability, poor selectivity and low adsorption capacity of traditional solid adsorbents, and achieve efficient adsorption and removal of thorium.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A N, O site functionalized COFs adsorption material, wherein the structures of the COFs are shown in Formulas I-III, and are named THz-DFDM COF, TAPT-TPT COF, and TAPT-DHTACOF, respectively:
[0008]
[0009] The preparation method of the N, O site functionalized COFs adsorption material comprises the following steps: adding an aldehyde monomer and an amino monomer into a Pyrex tube, adding an organic solvent for ultrasonic mixing, then adding a catalyst, placing the Pyrex tube in liquid nitrogen for freezing, evacuating and flame sealing the tube, heating for crystallization, Soxhlet extraction, washing and drying to obtain the N, O site functionalized COFs adsorption material.
[0010] Furthermore, the aldehyde monomer is one of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, and 2,5-dihydroxybenzene-1,4-dicarboxaldehyde; the amino monomer is one of 1,3,5-benzenetricarboxylic acid hydrazide and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.
[0011] Furthermore, the molar ratio of the aldehyde monomer to the amino monomer is 1 to 1.5:1.
[0012] Furthermore, the organic solvent is one or more of o-dichlorobenzene, N,N-dimethylacetamide, n-butanol, 1,4-dioxane, and mesitylene; the catalyst is an acetic acid aqueous solution, and the concentration of the acetic acid aqueous solution is 1 to 6 mol / L.
[0013] Furthermore, the ratio of the total mass of the aldehyde monomer and the amino monomer to the volume of the organic solvent is 30-55 mg: 0.5-3.0 mL; and the volume ratio of the catalyst to the organic solvent is 1:2.3-10.
[0014] Furthermore, the temperature of the heating crystallization reaction is 60 to 180° C., and the reaction time is 3 to 7 days.
[0015] Furthermore, the solvent used in the Soxhlet extraction is one or two of methanol and tetrahydrofuran.
[0016] A N, O site functionalized COFs adsorption material is prepared by any preparation method described in the present invention.
[0017] The invention provides an application of the N, O site functionalized COFs adsorption material in the adsorption of thorium.
[0018] Furthermore, the N, O site functionalized COFs adsorption material is used as an adsorbent in the adsorption of thorium.
[0019] Furthermore, the N, O site functionalized COFs adsorption material of the present invention is added into water to adsorb and enrich Th(IV), and the pH value of the adsorbed thorium ion solution is 1.0-5.0.
[0020] Furthermore, the pH value of the solution in which the N, O site functionalized COFs adsorption material adsorbs thorium ions is 3.0 to 5.0.
[0021] Furthermore, the pH value of the solution in which the N, O site functionalized COFs adsorption material adsorbs thorium ions is 4.0 to 5.0.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses aldehyde monomers and amino monomers containing N, O functional sites as raw materials to prepare a thorium adsorption material with excellent adsorption performance. The adsorption material of the present invention can quickly reach adsorption saturation within 1 hour due to the strong chelating coordination interaction between the N, O bidentate sites and thorium ions, thereby realizing the rapid removal of thorium ions.
[0024] The N, O site functionalized COFs adsorbent material prepared by the present invention has a unique affinity for Th(IV), has high metal ion selectivity and adsorption capacity, can be applied to thorium-containing wastewater with complex components, and the product is environmentally friendly. In addition, the N, O site functionalized COFs adsorbent material of the present application still has strong adsorption performance after multiple cycles of regeneration for adsorbing thorium, and the adsorbent material of the present invention has stable performance and high reuse rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The Fourier transform infrared (FT-IR) spectra of the N, O site functionalized COFs adsorption materials prepared in Examples 1, 2 and 3 of the present invention are shown; wherein (a) is the FT-IR spectrum of the THz-DFDM COF prepared in Example 1, (b) is the FT-IR spectrum of the TAPT-TPT COF prepared in Example 2, and (c) is the FT-IR spectrum of the TAPT-DHTA COF prepared in Example 3.
[0026] Figure 2 The PXRD spectra of the N, O site functionalized COFs adsorption materials prepared in Examples 1, 2 and 3 of the present invention; wherein (a) is the PXRD spectrum of the THz-DFDM COF prepared in Example 1, (b) is the PXRD spectrum of the TAPT-TPT COF prepared in Example 2, and (c) is the PXRD spectrum of the TAPT-DHTACOF prepared in Example 3.
[0027] Figure 3 These are SEM photographs of N, O site functionalized COFs adsorption materials prepared in Examples 1, 2, and 3 of the present invention; wherein (a) is a SEM photograph of the THz-DFDM COF prepared in Example 1, (b) is a SEM photograph of the TAPT-TPT COF prepared in Example 2, and (c) is a SEM photograph of the TAPT-DHTACOF prepared in Example 3.
[0028] Figure 4 The figures are graphs showing the adsorption of Th(IV) by the N, O site functionalized COFs adsorption materials prepared in Examples 1, 2 and 3 of the present invention under different pH conditions; wherein, (a) is a graph showing the adsorption of Th(IV) by the THz-DFDM COF prepared in Example 1, (b) is a graph showing the adsorption of Th(IV) by the TAPT-TPT COF prepared in Example 2, and (c) is a graph showing the adsorption of Th(IV) by the TAPT-DHTACOF prepared in Example 3.
[0029] Figure 5 This is the adsorption kinetics diagram of thorium by TAPT-DHTA COF prepared in Example 3 of the present invention.
[0030] Figure 6 This is a graph showing the adsorption capacity of TAPT-DHTACOF prepared in Example 3 of the present invention for multi-component competing ions.
[0031] Figure 7 This is a graph showing the recycling performance of the TAPT-DHTA COF prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0033] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0034] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0035] The Pyrex tube of the present invention has a diameter of 26 mm, a length of 125 mm, and a capacity of 10 mL.
[0036] Example 1 Preparation of THz-DFDM COF Material
[0037] 2,5-Dimethoxybenzene-1,4-dicarboxaldehyde (0.075mmol) and 1,3,5-benzenetricarboxylic acid hydrazide (0.075mmol) were added to a 10mL Pyrex tube, and 2mL of an organic solvent mixed with 1,4-dioxane and mesitylene in a volume ratio of 1:3 was added for ultrasonication for 15min, and 0.2mL of a 6mol / L acetic acid aqueous solution as a catalyst was added. The Pyrex tube was then placed in liquid nitrogen and rapidly frozen at 77K. After degassing by three freeze-pump-thaw cycles, the tube was evacuated under vacuum and sealed with a flame, and heated at 120°C for 3 days. The obtained solid was subjected to Soxhlet extraction with anhydrous tetrahydrofuran (5mL) for 24h, and then vacuum dried at 100°C for 8 hours to obtain a yellow solid powder, named THz-DFDM COF. The yield of the THz-DFDM COF material was 72%, and the BET specific surface area was 187m 2 / g, pore volume 0.3cm 3 / g. Figure 1 As shown in (a), the information analysis results obtained by FT-IR spectrum: after the reaction, the -1 and 3388cm -1 The signal peaks at 1545cm -1 A stretching vibration peak corresponding to C=N appeared at , proving that the two monomers underwent Schiff base polycondensation reaction to successfully form an imine linker.
[0038] Example 2 Preparation of TAPT-TPT COF Materials
[0039] 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (0.05mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (0.05mmol) were added to a 10mL Pyrex tube, 0.5mL of an organic solvent mixed with o-dichlorobenzene and n-butanol in a volume ratio of 1:1 was added, and ultrasonication was performed for 15min. 0.05mL of a 6mol / L acetic acid aqueous solution as a catalyst was added, and then the Pyrex tube was placed in liquid nitrogen and rapidly frozen at 77K. After degassing by three freeze-pump-thaw cycles, the tube was evacuated under vacuum and sealed with a flame, heated at 60°C for 1 day, and Soxhlet extraction was performed with tetrahydrofuran (5mL) for 24h, and then vacuum-heated and dried at 90°C for 12h to obtain a white powder named TAPT-TPT COF. The yield of the TAPT-TPT COF material was 71%, and the BET specific surface area was 1802.5m 2 / g. Figure 1 (b) shows the information analysis results obtained by FT-IR spectrum: the sample after reaction has a peak at 1614 cm -1 An infrared absorption peak corresponding to the C=N bond appeared at , indicating the formation of an imine linking bond.
[0040] Example 3 Preparation of TAPT-DHTACOF material
[0041] 2,5-Dihydroxybenzene-1,4-dicarboxaldehyde (0.13mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (0.09mmol) were added to a 10mL Pyrex tube, and 2mL of an organic solvent mixed with o-dichlorobenzene and N,N-dimethylacetamide in a volume ratio of 9:1 was added and ultrasonicated for 15min. Then, 0.2mL of a 6mol / L acetic acid aqueous solution as a catalyst was added, and the mixture was rapidly frozen at 77K. After degassing by three freeze-pump-thaw cycles, the mixture was evacuated under vacuum and sealed with a flame, and heated at 120°C for 3 days. The obtained solid was subjected to Soxhlet extraction with anhydrous tetrahydrofuran (5mL) for 24h, and then vacuum dried at 120°C overnight to obtain a red solid powder, which was named TAPT-DHTA COF. The yield of the TAPT-DHTA COF material was 70%, and the BET specific surface area was 787m 2 / g, pore volume 0.61cm 3 / g. Figure 1 (c) shows the information analysis results obtained by FT-IR spectrum: at 1614cm -1 An infrared absorption peak corresponding to the C=N bond appeared at , indicating that the imine bond was successfully formed.
[0042] In addition, the THz-DFDM COF material, TAPT-TPT COF material and TAPT-DHTACOF material prepared in Examples 1-3 were subjected to powder XRD ray diffraction test. The results are as follows: Figure 2 As shown. Figure 2 It can be observed that all three materials have obvious characteristic diffraction peaks, indicating that the prepared N, O site functionalized COFs adsorption materials have high crystallinity. The three materials were tested by scanning electron microscopy (SEM), and the results are as follows Figure 3 As shown. Figure 3 It can be seen that the morphologies of the three synthesized materials are regular and orderly, among which THz-DFDM COF has a nanorod-like structure, TAPT-TPT COF has a nanosphere-like structure, and TAPT-DHTA COF has a fiber mesh structure.
[0043] Example 4 Thorium adsorption experiment of N, O site functionalized COFs adsorption material at different pH values
[0044] The N, O site functionalized COFs adsorption material prepared in Example 1-3 was used for thorium adsorption experiment at room temperature. A thorium solution with an initial concentration of 100 ppm was taken as the test solution, and 0.1 mol / L nitric acid and / or 0.1 mol / L sodium hydroxide solution were added dropwise to adjust the pH value of the test solution to 1.0, 2.0, 3.0, 4.0 and 5.0, and then the N, O site functionalized COFs adsorption material prepared in Example 1-3 was added as an adsorbent to the test solution for adsorption test. The mass ratio of the adsorbent and the volume of the test solution was 2 mg: 6 mL, and the adsorption contact time was 24 h. After 24 h, the adsorption solution was filtered with a filter membrane, and the concentration of thorium ions before and after adsorption was determined by full spectrum inductively coupled plasma emission spectroscopy. The experimental results are as follows: Figure 4 shown.
[0045] Depend on Figure 4 It can be seen that the adsorption performance of N, O site functionalized COFs adsorption materials THz-DFDM COF, TAPT-TPT COF, and TAPT-DHTACOF gradually increases under the conditions of pH 1.0-3.0, and all reach the maximum adsorption amount at pH = 4.0, and reach adsorption saturation at this initial concentration.
[0046] Example 5N, adsorption isotherm experiment of thorium on O-site functionalized COFs adsorption material
[0047] From the experiment of Example 4 above, it can be seen that the optimal pH value for thorium adsorption is 4.0. Therefore, the maximum saturated adsorption capacity of three N, O site functionalized COFs adsorption materials was tested at a thorium solution pH = 4.0. The initial concentration of thorium ions was 25-400 ppm, the adsorption time was 24 h, and the adsorption solution was filtered with a filter membrane after adsorption. The concentration of thorium ions before and after adsorption was determined by full spectrum inductively coupled plasma emission spectroscopy. The experimental results are shown in Table 1.
[0048] Table 1 Maximum saturated adsorption of thorium by N, O site functionalized COFs adsorption materials at pH = 4.0
[0049]
[0050] It can be seen from Table 1 that the material of Example 3 has a higher saturated adsorption capacity, reaching 1394 mg / g, while the adsorption capacities of Examples 1 and 2 are 1233 and 679 mg / g, respectively.
[0051] Example 6 Adsorption kinetics experiment of TAPT-DHTACOF material
[0052] From the experiment of Example 5 above, it can be seen that the TAPT-DHTACOF material prepared in Example 3 has a higher saturated adsorption capacity. Therefore, the TAPT-DHTA COF material prepared in Example 3 was subjected to an adsorption kinetics experiment, the thorium ion solution pH = 4.0, the initial concentration was 100 ppm, the adsorption time was 1 min to 24 h, and the adsorption solution was filtered with a filter membrane after adsorption. The concentration of thorium ions before and after adsorption was determined by full spectrum inductively coupled plasma emission spectroscopy. The experimental results are shown in FIG. Figure 5 shown.
[0053] Depend on Figure 5 It can be seen that TAPT-DHTA COF material can be rapidly adsorbed within 1 minute and reach adsorption saturation within 1 hour.
[0054] Example 7 Metal ion coexistence adsorption experiment of TAPT-DHTA COF material
[0055] From the experiments of Examples 5 and 6 above, it can be seen that the TAPT-DHTA COF material prepared in Example 3 has a higher adsorption amount and adsorption rate. Therefore, a multi-component metal ion coexistence adsorption experiment was conducted on the TAPT-DHTA COF material prepared in Example 3. Thorium (Th 4+ ), uranyl (UO2 2+ ), Lanthanum (La 3+ ), praseodymium 3+ ), Samarium (Sm 3+ ), Europium 3+ ), Gadolinium (Gd 3+ ), Lu3+ ), rubidium (Rb + ) Different metal ions coexist in a mixed solution. The concentration of each metal ion is 100ppm. The volume of the mixed solution is 6mL. 2mg of TAPT-DHTA COF material is added to the mixed solution for adsorption for 2h. The adsorption effect of different metal ions is measured. The experimental results are as follows: Figure 6 shown.
[0056] Depend on Figure 6 It can be seen that in an environment where multiple metal ions coexist, the TAPT-DHTACOF material prepared in Example 3 of the present invention has a strong affinity for Th. 4+ The ions have strong affinity and high selectivity, so the thorium adsorption material of the present invention has excellent adsorption performance for thorium.
[0057] Example 8: Verification of the recycling performance of TAPT-DHTACOF material
[0058] The TAPT-DHTA COF material prepared in Example 3 was subjected to a recycling experiment. Under room temperature conditions, the TAPT-DHTA COF material was mixed with a 100 ppm Th(IV) solution in a ratio of 20 mg:60 mL for adsorption. The TAPT-DHTA COF material after 24 hours of adsorption was immersed in a 0.1 mol / L HNO3 aqueous solution for 24 hours (solid-liquid ratio of mg / mL=1:5), filtered, and washed with deionized water until the supernatant was neutral. After vacuum drying, the recycled sample was obtained and subjected to the next round of adsorption. The adsorption effect of thorium after 5 cycles of regeneration was measured. The experimental results are as follows: Figure 7 shown.
[0059] pass Figure 7 It can be seen that the thorium adsorbent of the present invention still has strong adsorption performance after 5 cycles of regeneration, which shows that the adsorption material of the present invention has stable performance and high reuse rate.
[0060] Comparative Example 1
[0061] Compared with Example 3, the process parameters in the preparation process of TAPT-DHTA COF material in this comparative example are changed, and the rest are the same as Example 3. The preparation method of TAPT-DHTA COF material in this comparative example is:
[0062] 2,5-dihydroxybenzene-1,4-dicarboxaldehyde (0.05mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (0.09mmol) were added to a 10mL Pyrex tube, 1mL of an organic solvent mixed with o-dichlorobenzene and N,N-dimethylacetamide in a volume ratio of 9:1 was added, ultrasonication was performed for 15min, 0.2mL of a 3mol / L acetic acid aqueous solution as a catalyst was added, and the mixture was rapidly frozen at 77K, degassed by two freeze-pump-thaw cycles, and then vacuumed and flame-sealed, and heated at 90°C for 3 days. The obtained solid was subjected to Soxhlet extraction with anhydrous tetrahydrofuran (5mL) for 24h, and then vacuum dried at 80°C overnight to obtain a red solid powder named TAPT-DHTA COF-2. The yield of the TAPT-DHTA COF-2 material was 52%. The TAPT-DHTA COF-2 material prepared in this comparative example was used to adsorb a thorium solution with an initial concentration of 400 ppm, and the adsorption amount after 24 hours was 421 mg / g. It can be seen that the yield and adsorption amount of the TAPT-DHTA COF-2 material prepared in this comparative example are significantly worse than those in Example 3.
[0063] Comparative Example 2
[0064] Compared with Example 3, the aldehyde monomer and the amino monomer raw materials were changed in the preparation process of this comparative example, and the rest was the same as Example 3. The preparation method of this comparative example is:
[0065] 1,3,6,8-tetrakis(p-tolylphenyl)pyrene (0.13mmol) and p-phenylenediamine (0.09mmol) were added to a 10mL Pyrex tube, 2mL of an organic solvent mixed with o-dichlorobenzene and N,N-dimethylacetamide in a volume ratio of 9:1 was added, and ultrasonication was performed for 15 minutes, and then 0.2mL of 6mol / L acetic acid as a catalyst was added, and the mixture was rapidly frozen at 77K, degassed by 3 freeze-pump-thaw cycles, and then vacuumed and flame-sealed, and heated at 120°C for 3 days. The obtained solid was subjected to Soxhlet extraction with anhydrous tetrahydrofuran (5mL) for 24h, and then vacuum dried at 120°C overnight to obtain a solid powder, named A COF. The yield of the A COF material was 58%, and the A COF material prepared in the comparative example was used for the adsorption of a thorium solution with an initial concentration of C0 of 400ppm, and the adsorption amount after 24h was 387mg / g. It can be seen from this that the yield and adsorption capacity of the ACOF material prepared in this comparative example are significantly worse than those in Example 3.
[0066] In summary, the thorium adsorption material prepared by the present invention has excellent adsorption performance, thorium selectivity, good material stability and high reuse rate.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A N, O site functionalized COFs adsorption material, characterized in that: The structures of the COFs adsorption materials are shown in the following formulas Ⅰ-Ⅲ, which are named THz-DFDM COF, TAPT-TPT COF, and TAPT-DHTACOF respectively:
2. The method for preparing the N, O site functionalized COFs adsorption material according to claim 1, characterized in that: The following steps are involved: The aldehyde monomer and the amino monomer are added into a Pyrex tube, an organic solvent is added and ultrasonically mixed evenly, a catalyst is added, the Pyrex tube is placed in liquid nitrogen for freezing, vacuumized and flame-sealed, and the N, O site functionalized COFs adsorption material is obtained by heating for crystallization, Soxhlet extraction, washing and drying.
3. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The aldehyde monomer is one of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, and 2,5-dihydroxybenzene-1,4-dicarboxaldehyde; the amino monomer is one of 1,3,5-benzenetricarboxylic acid hydrazide and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.
4. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The molar ratio of the aldehyde monomer to the amino monomer is 1-1.5:
1.
5. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The organic solvent is one or more of o-dichlorobenzene, N,N-dimethylacetamide, n-butanol, 1,4-dioxane, and mesitylene; the catalyst is an acetic acid aqueous solution, and the concentration of the acetic acid aqueous solution is 1-6 mol / L.
6. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The ratio of the total mass of the aldehyde monomer and the amino monomer to the volume of the organic solvent is 30-55 mg: 0.5-3.0 mL; the volume ratio of the catalyst to the organic solvent is 1:2.3-10.
7. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The temperature of the heating crystallization reaction is 60-180° C., and the reaction time is 3-7 days.
8. The method for preparing the N, O site functionalized COFs adsorption material according to claim 2, characterized in that: The solvent used in the Soxhlet extraction is one or two of methanol and tetrahydrofuran.
9. Use of the N, O site functionalized COFs adsorption material according to claim 1 or the N, O site functionalized COFs adsorption material prepared by the preparation method according to any one of claims 2 to 8 in the adsorption of thorium.
10. The use according to claim 9, characterized in that: The pH value of the solution in which the N, O site functionalized COFs adsorption material adsorbs thorium ions is 1.0-5.0.
Citation Information
Patent Citations
Preparation method of porous covalent organic framework and application of porous covalent organic framework in uranyl ion capture
CN113045723A
Triazinyl covalent organic framework material as well as preparation method and application thereof
CN117209698A
Covalent organic framework adsorbent, preparation method and application
CN117700659A
Covalent-Organic Framework Materials and Methods of Making Thereof
US20220323935A1
